Implementasi Etika Administrasi untuk Meningkatkan Kualitas Pelayanan Publik di Kantor Camat Padang Utara, Kota Padang - Hanum, Nurfadillah; Rahmi, Ranti Sania; Aflah, Dzakiyah; Ferdiansyah, Ferdiansyah; Hanoselina, Yulia; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study aims to analyze the application of administrative ethics in improving the quality of public services at the Padang Utara Sub-District Office, Padang City. The research informants include the Head of Tranquility, Public Order, and Disaster Management Division, personnel managers, the general public, and service recipients. This research adopts a qualitative descriptive approach using interview, observation, and documentation techniques. The indicators used include equality, equity, loyalty, and responsibility. The findings indicate that the implementation of administrative ethics at the Padang Utara Sub-District Office has been conducted effectively. However, several challenges, such as limited human resources and a lack of regular training, were identified. Therefore, strengthening ongoing administrative ethics training is necessary to ensure courteous, fair, and professional service quality.